PENGARUH PENDIDIKAN KESEHATAN MEDIA BOOKLET TERHADAP PENGETAHUAN DAN SIKAP KELUARGA TENTANG SPEECH THERAPY PADA PASIEN STROKE DI IRNA SERUNI A RSUD DR. SOETOMO SURABAYA (The Influence Of Health Education With Booklet Media On Knowledge And Attitudes Towa - Nimah, Lailatun; Nurwahyuni, Tutuk; Wahyuni, Erna Dwi (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2018)
Introduction: Stroke included into the blood vessel disease. Stroke is the leading cause ofcommunication disorder that aphasia and dysarthria. Speech therapy is absolutely necessary to overcome communication disorders. Family empowerment through health education is very important to optimize speech therapy. This study aimed to determine the influence of health education with booklets on knowledge and attitudes of families of stroke on speech therapy at IRNA Seruni A Hospital Dr. Soetomo Surabaya. Method: The design of this study is pre-experimental with intervention Health education use booklet, design were analyzed by Wilcoxon sign rank test. The population in this study were all cases of stroke. The sampel in this study were the patient’s familiy with aphasia five person and dysartria 11 person who taken by consecutive sampling. Independent variables was health education with booklet media and dependent variable were the knowledge and attitude.Result: The results showed that the health education with booklet media about speech therapyhas significant influence to improve the knowledge (aphasia p = 0,038; dysartria p = 0,003) dan attitude (aphasiap = 0,042; dysartriap = 0,003)..Instrument use questionare. Discussion: It can be concluded that health education with booklet media on speech therapyhas influence in increasing of knowledge and attitudes of families on speech therapy. therefore, for future research needs to do research on the effect of health education with booklet media on behavior / psychomotor family of speech therapy.